Towards a New Macroeconomics. From ISLM-AS and DSGE to GSMS and GSMS-SS - Mueller, Antony Peter (2014)
Different from conventional macroeconomic models, which start from the presumption that the economy is permanently in need of control and repair, the goods side/money side (GSMS) approach is not a tool to guide policy intervention but aims at demonstrating how the economy works. As such, the model provides an explanatory framework that should be particularly useful for business and finance, while the message for policy makers is mainly what not to do. The GSMS approach avoids the ambiguities about flexibility or rigidity of the price level, real and nominal variables and the short and the long run that plague ISLM-AS analyses. With business activity as the micro-foundation of the GSMS model, the approach does away with the surreal assumptions of DSGE models. In its GSMS-SS version, the model connects the short run with the long run laying the groundwork for a novel way of business cycle analysis. The GSMS and GSMS-SE models facilitate the teaching of macroeconomics and provide the tools for the systematic analysis of macroeconomic configurations and policy concepts.